MANAJEMEN PEMBERDAYAAN KURIKULUM DALAM MENINGKATKAN MUTU PENDIDIKAN - Samsidar Samsidar (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2016)
Curriculum is all of the experiences that already planned to prepare the students in achieving the goal of education. The curriculum planning needs collection, formation,selection of related information from various resources. Afterwards, the information will use to design the learning experience so that students can achieve the goal of curriculum. There are some efforts of school curriculum must be provide such as a competent and professional teacher with appropriate education background to the subject in teaching, society and parents support, then the available references inIndonesian, Arabic and English language.